2005
DOI: 10.1104/pp.105.065961
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptional Profiling of Two Contrasting Rice Genotypes under Salinity Stress during the Vegetative Growth Stage

Abstract: Rice (Oryza sativa), a salt-sensitive species, has considerable genetic variation for salt tolerance within the cultivated gene pool. Two indica rice genotypes, FL478, a recombinant inbred line derived from a population developed for salinity tolerance studies, and IR29, the sensitive parent of the population, were selected for this study. We used the Affymetrix rice genome array containing 55,515 probe sets to explore the transcriptome of the salt-tolerant and salt-sensitive genotypes under control and salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
297
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(338 citation statements)
references
References 62 publications
37
297
2
2
Order By: Relevance
“…There was an apparently delayed response to cold in K354 compared with C418, with 232 DEGs in C418 vs 83 in K354 at 2 h cold stress. Similar results were previously observed in rice under salinity stress; in that study, the sensitive genotype IR29 induced a relatively large number of genes compared to tolerant FL478 [18]. In addition, comparison of gene expression levels between K354 and C418 showed that there were 308 up-regulated and 209 down-regulated genes in K354 compared with C418 under control conditions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…There was an apparently delayed response to cold in K354 compared with C418, with 232 DEGs in C418 vs 83 in K354 at 2 h cold stress. Similar results were previously observed in rice under salinity stress; in that study, the sensitive genotype IR29 induced a relatively large number of genes compared to tolerant FL478 [18]. In addition, comparison of gene expression levels between K354 and C418 showed that there were 308 up-regulated and 209 down-regulated genes in K354 compared with C418 under control conditions.…”
Section: Resultssupporting
confidence: 88%
“…Although high-throughput RNA sequencing has recently become popular as an alternative to microarray analysis, the microarray platform, with its robust sample process and data analysis pipelines, is still the preferred choice for transcriptomic profiling involving a large number of samples in model plants with well-annotated genomes [14,15]. Many microarray-based studies have been carried out to identify abiotic stress responsive genes in specific rice varieties and transgenic rice [9,10,16,17], and comparative transcriptional profiling of two contrasting rice genotypes under salinity and drought stress have revealed novel genetic regulatory mechanisms involved in stress tolerance [18,19]. Unfortunately, it is difficult to use the stress-related genes uncovered in those studies to improve modern varieties in rice breeding, because most of them already exist in elite rice varieties.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant potential is highly variable in different plant species and in different genotypes of the same species. Stress tolerant genotypes have often been reported to show higher expression of antioxidants as reported for salt (Walia et al, 2005), drought (Türkan et al, 2005), cold (Seppanen and Coleman, 2003,b;Kumar et al, 2008a,b;Mutlu et al, 2013) and heat stress (Snider et al, 2010;Almeselmani et al, 2009). The responsiveness and efficiency of scavenging systems of plants governs their performance, endurance, and survival capability under stress conditions (Seppanen and Coleman, 2003;Mishra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Image-based phenotyping for non-destructive screening of different salinity tolerance traits in rice shoots was used (Hairmansis et al, 2014). The imaging techniques for seed germination to identify salt-tolerant genotypes can be useful, especially when seeds have different colors and phenotype (Walia et al, 2005;Li et al, 2016). At the leaf scale, it was found that hyperspectral reflectance and chlorophyll fluorescence can be served as valuable tools for non-invasive measurements of photosynthetic parameters under salinity stress (Li et al, 2010).…”
Section: Integration Of Hyperspectral Analyses Into Salt-stress Relatmentioning
confidence: 99%